Pengaruh Konsentrasi Pupuk STMJ Plus (Susu Telur Molase Jamur Trichoderma sp. dan Limbah Buah-Buahan) terhadap Pertumbuhan dan Hasil Dua Varietas Selada (Lactuca sativa L.): Pengaruh Konsentrasi Pupuk STMJ Plus (Susu Telur Molase Jamur Trichoderma sp. dan Limbah Buah-Buahan) terhadap Pertumbuhan dan Hasil Dua Varietas Selada (Lactuca sativa L.) - Ummah, Anisatul; Arum, Ayu Puspita; Setiyono, Setiyono; Fanata, Wahyu Indra Duwi; Tanzil, Ahmad Ilham (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Increasing lettuce production will be done by improving cultivation inputs, such as increased nutritional needs. An alternative organic fertilizer that can be used is made from spoiled milk, eggs, Trichoderma sp. molasses, and fruit waste, or STMJ Plus for short. STMJ Plus Fertilizer acts as an organic nutrient to encourage plant growth. This study aimed to determine the effect of the interaction between STMJ Plus fertilizer concentrations and lettuce varieties on the growth and yield of lettuce plants. The experiment was carried out in a factorial manner using a completely randomized design (CRD) consisting of 2 factors with 4 replications. The first factor is the concentration of STMJ Plus fertilizer consisting of 4 levels: P0: without fertilizer; P1: 5 ml L-1; P2: 10 ml L-1; and P3: 15 ml L-1. The second factor was the variety, which consisted of 2 levels: V1: Grand Rapids and V2: Red Rapid. The results of this study that the interaction of STMJ Plus fertilizer concentrations and lettuce varieties showed highly significant differences in plant height and plant fresh weight variables. The combination that gave the best effect was the concentration of 15 ml L-1 on the Red Rapid (P3V2).